New tools for personalised nutrition: The Food4Me project. Issue 2 (June 2015) - Ryan, N. M.; O'Donovan, C. B.; Forster, H.; Woolhead, C.; Walsh, M. C.
Abstract Personalised nutrition can be considered on three levels, with nutritional advice tailored according to an individual's dietary intake, phenotype or genotype. Personalised nutrition has the potential to become an effective strategy for improving dietary behaviours, with numerous studies demonstrating that personalised advice is more effective than generic advice. Although personalised nutrition is in its early stages, recent advances in technology and research innovation have led to an evolution in both the assessment and delivery of personalised nutrition advice. This report outlines some of the various techniques being explored as part of the Food4Me project.